ANALISIS TINGKAT KESADARAN PETANI PADI DALAM MEMBAYAR ZAKAT PERTANIAN (Studi Kasus di Desa Kaibonpetangkuran Kecamatan Ambal Kabupaten Kebumen) - Fatkurohmah Titin Lailiah; Ubaidillah Ubaidillah (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Agricultural zakat is zakat produced from agricultural products in the form of crops such as rice, corn and wheat. Rice farmers' awareness of paying agricultural zakat is very important because agricultural zakat is obligatory for every Muslim who, if they have fulfilled the requirements, is obliged to pay zakat on their harvest. Seeing that many farmers have reached the nisab for their agricultural produce, there are quite a few who do not know and understand agricultural zakat itself, which causes farmers not to pay agricultural zakat. This research aims to determine the level of awareness of rice farmers in paying agricultural zakat and what factors influence the low awareness of farmers in paying agricultural zakat in Kaibonpetangkuran Village, Ambal District, Kebumen Regency. This research uses descriptive qualitative analysis methods with field research methods. Then, data collection techniques through observation, interviews and documentation. Meanwhile, the analysis method used is using data reduction, presenting data, and drawing conclusions. The results of this research show that the level of awareness of rice farmers in paying agricultural zakat in Kaibonpetangkuran Village, Ambal District, Kebumen Regency is still very low and is included in the level of awareness of Unconscious Incompetence, namely the first stage where a person does not understand what to do. This is because most farming communities are still guided by their habit of giving their harvest to the residents around them. Then, there are factors that influence farmers' low awareness, namely socialization factors, income factors, education and knowledge factors, and habit factors.